Perkecambahan Biji dan Pertumbuhan Semai Kakao (Theobroma cacao L.) Asal Sulawesi Tengah yang Dibudidayakan di Kabupaten Banyumas Jawa Tengah - Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
A new area plantation began to grow a new plant species usually do not have a stock of seed that must be imported from outside. Shipping seeds from outside the lower viability at risk. Seed deterioration can be caused by mechanical or physiological damage and very decisive phase of growth and development of the next crop. One way to know the quality is by knowing the percentage of seed germination and seedling growth. This study aims to identify the seed germination and seedling growth of cocoa (Theobroma cacao L.) from Sulawesi, which is planted in the area of Central Java Banyumas. The results show the origin of cocoa beans grown in the Central Sulawesi district of Banyumas can germinate all at day 27 where a good germination of 77.53% and 32.47% unfavorable, while the growth of seedlings until week 10 showed normal seedling growing reached 78.41% and 21.59% poor. Growth of cocoa seedling on medium for 8-week weaning obtained plants with 24-34 cm high and 11 leaves.